Nanoscale hydrophilic colloids with high relaxivity and low cytotoxicity based on Gd(iii) complexes with Keplerate polyanions. (13th June 2017) - Elistratova, Julia; Akhmadeev, Bulat; Gubaidullin, Aidar; Korenev, Vladimir; Sokolov, Maxim; Nizameev, Irek; Stepanov, Alexey; Ismaev, Ildus; Kadirov, Marsil; Voloshina, Alexandra; Mustafina, Asiya
Abstract : Efficient hydrophilic stabilization of Gd(iii ) complexes with Keplerate polyanions for high relaxivity, colloid stability and low cytotoxicity. Abstract : The work introduces for the first time Mo-132-type Keplerates (Kp) and Gd 3+ ions as a basis for the one-pot synthesis of aqueous colloids with high longitudinal relaxivity ( r 1 = 96.4 mM −1 s −1 at 20 MHz). The hydrophilic coating of small (3–5 nm) Gd x (Kp) y -based cores provides their colloid stabilization, protection from degradation and low cytotoxicity.